PHYSIOLOGICAL STUDIES OF SOME THERMOPHILIC FUNGI ISOLATED FROM AGRICULTURAL PRODUCTS FROM DHARWAD, KARNATAKA, INDIA. - CH. RAMESH; ANILKUMAR K. HEGDE (International Journal of Pharma and Bio Sciences, 2014)
Physiological studies of some Thermophilic fungi which were isolated in the present study of the different regions of Dharwad, Karnataka, India viz; Mucor miehei, Mucor pusillus, Chaetomium thermophile var. coprophile, Chaetomium thermophile var. thermophile, Aspergillus flavus, Humicola grisea var. thermoidea, Humicola insolens, Humicola lanuginosa, Malbranchea pulchella var. sulfurea, Paeciliomyces varioti, Penicillium duponti and Torula thermophila etc. Which were isolated by dilution plate technique. The present study was concentrated on the growth of above fungi on different media and also the effect of different Carbon and Nitrogen sources. All the experiments are conducted on both broth cultures as well as agar media in triplicates for each substrate. The results obtained in this study were compared with the similar studies carried out and discussed.